(untitled) (Scientific journal of the Fergana State University, 2026)
The interaction products of chitosan and ethylenediaminetetraacetic acid (EDTA) are often used for the preparation of solid and hydrogel membranes. In this study, we aimed to carry out the reaction between chitosan and EDTA in solution, in contrast to the traditional solid-phase conditions that require high temperatures and shear deformations. The reaction proceeds via an addition/elimination mechanism, in which the amide function of the amino groups is restored and amides are formed. Comparison of the infrared spectra, X-ray diffraction patterns, and electron microscopy data of chitosan and the obtained product demonstrated that the reaction proceeded to a sufficient extent. To obtain the N-acylation product with EDTA, chitosan from Eurygaster integriceps with a molecular weight of 93.07 kDa and a degree of deacetylation of 91.6% was used. As a result of the experiments, it was established that the optimal conditions for the N-acylation reaction of chitosan with EDTA are a temperature of 40 ºC and a duration of 4 hours. Under these conditions, the product yield was 42.6%.